Residential location influences travel - but how and why? - Næss, Petter (Proceedings from the Annual Transport Conference at Aalborg University, 2002)
Investigations in a number of cities and metropolitan areas have shown that those living in the outer, low-density parts travel considerably longer by motorized means of transportation, compared to the residents of inner and central parts of the town. The same main pattern has been found in cities as different as Paris (Mogridge, 1985; Fouchier 1998), London (Mogridge, ibid.), New York and Melbourne (Newman and Kenworthy, 1989), San Fransisco (Schipper et al., 1994), Greater Oslo (Næss, Røe and Larsen, 1995; Røe 1999), Bergen (Duun, 1994), and Trondheim (Synnes, 1990). However, many of the early empirical studies demonstrating correlations between urban structure and travel behavior have been criticized for not taking into consideration socioeconomic factors and/or disregarding the influence of the travelers’ attitudes and lifestyles. Because, among other things, the income levels, household structures, age and leisure interests of the inhabitants often vary between inner and outer parts of the city, there is a risk that differences in the transportation pattern actually caused by such factors are being explained with differences in the location. In some studies, attempts have been made to meet these points of criticism by including socioeconomic variables in the analyses (e.g. Næss, Røe and Larsen, ibid.), and in a few studies also indicators of the travelers’ attitudes and lifestyles (e.g. Røe, ibid.). Still, some critics call attention to the fact that statistical correlations, even with multivariate control, can never establish whether a causal relationship exists between urban structure and travel behavior. In order to meet the above criticisms, a comprehensive study of urban structure and transport has recently been conducted in the Copenhagen area, aiming to identify the overall relationships as well as the more detailed mechanisms through which the location of residences within the metropolitan area influences travel behavior. In the remaining part of this paper, the theoretical basis, research questions and methods the Copenhagen area study will first be discussed. A number of mechanisms through which residential location affects travel behavior will then be identified, drawing mainly on qualitative interviews. Thereupon, the question of which mechanisms and influences are the dominating ones will be addressed, based on statistical analyses of data from two comprehensive travel surveys.